FAKTOR - FAKTOR YANG MEMPENGARUHI KONVERSI LAHAN PERTANIAN SERTA DAMPAKNYA TERHADAP KESEJAHTERAAN PETANI DI KABUPATEN KUBU RAYA (Studi Kasus di Desa Sungai Raya, Kecamatan Sungai Raya) - B01111015, Rikardus Roli (Jurnal Pembangunan dan Pemerataan, 2015)
This research is aimed to know the factors affecting agricultural land conversion and its impact farmers welfare in Regency Kubu Raya(Case Studies in Sungai Raya district of Sungai Raya)Conversion phenomenon is basically the result of the competition between agricultural land use to non - agricultural sector arising from the three economic and social phenomenon are limited natural resources, population growth and economic growth.The method used in this study is a descritive method. Sources of data used in this study using primary data source is by distributing questionnaires directly to farmers and secondary data sources to find data from BPS and other relevant sources. Sampling of the population is performed using Slovin formula. Data analysis method used is the method of SWOT analysis.Research results obtained are all variables affect the conversion. There are just external factors have a significant effect. The variable is the soil quality, housing needs, and the opportunity to buy land elsewhere. Suggestion for reducing land conversion is the government should reinforce the regulations in the field of licensing, especially to build in wetland.Keywords : Land Conversion, Land, Farmer Welfare.